KONTRADIKSI DASAR PENGENAAN PAJAK PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 - Puan Indri Hazimah Indri Hazimah; Ferry Irawan (Universitas Pamulang, 2018)
AbstractThis research tries to elaborate the contradiction between Government Regulation number 46 of 2013 (PP 46/2013) and Article 4 paragraph 1 Law number 36 of 2008 (Income Tax Law) in addressing tax base. Also, it describes income tax simulation from PP 46/2013 an Income Tax Law perspective. This research is designed by applying literature review and field study method. We collect and analysis data throughout laws, text-books, and journals to obtain a a suitable framework related to the case discussed. Furthermore, we also conduct interview to find practical experience that cannot be found in literatures. A deep-interview is applied to the relevant officials. The result shows that usage of gross revenue to calculate tax base based on PP 46/2013 is quite suitable with the objective of the regulation, to simplify and support tax payers in fulfilling their tax-obligation. On the other hand, although the revenue is not appropriate with the definition of Income tax law, every additional economic capability, the provision is not against general rules. This is occurred because Article 17 paragraph 7 and Article 4 paragraph 2 letter (a) Income Tax Law allow certain income will be imposed by final income tax. Keyword: Tax Base, Income, Gross Revenue, PP 46/2013